Preliminary theoretical design of crossflow water turbine for rainwater rooftop harvesting system - Suhaimi, Mohamed Aidil; Mat Tokit, Ernie; Mohd Sa'at, Fatimah Al-Zahrah; Mohd Rosli, Mohd Afzanizam; Herawan, S. G.; Oktarina, R.; Setyandito, O. (2023)
Harvesting energy is essential especially now that the demand of energy is high but the fuel supply is limited. This study theoretically designs the 5 m low head crossflow turbine in rainwater harvesting system. The characteristics of the site condition, the runner geometry, the blade geometry, and the turbine specification had been identified and the geometrical model of the design is shown. This paper reported the collection of theoretical formula for the design of low head crossflow turbine that can be used for rainwater harvesting system. The dimensional form of equations, as presented in Section 2, resulted to the two, four, and two parameters that represent the dimensions of the turbine, runner and the blade, respectively. As a conclusion, the designed turbine can be used for rainwater harvesting system with an efficiency that was calculated to be 88% with 22 kW expected power generated for 5 m head.